JOB SATISFACTION AND TURNOVER INTENTION WITH POSITIVE AFFECT AS MODERATING VARIABLE: GENDER PERSPECTIVE - Muhammad Asril Arilaha, Johan Fahri, Irfandi Buamonabot (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study seeks to investigate the effect of positive affect moderation on the relationship between job satisfaction and turnover intention based on gender. A total of 102 employees working for motorcycle dealers were involved in this survey. The effective rate of return in this study was 82%. A hierarchical regression analysis was used in this study. The results showed that positive affect based on gender, particularly female gender, strengthened the relationship between job satisfaction and turnover intention compared to male gender. Implications and suggestions for future research are discussed in this study